Detection of cavernous transformation of the portal vein by contrast-enhanced ultrasound - Hwang, Misun (J Ultrasound, 2018)
PURPOSE: Cavernous transformation of the portal vein can be missed on color Doppler exam or arterial phase cross-sectional imaging due to their slow flow and delayed enhancement. Contrast-enhanced ultrasound (CEUS) offers many advantages over other imaging techniques and can be used to successfully detect cavernous transformations of the portal vein. METHODS: A 10-month-old female was followed for repeat episodes of hematemesis. Computed tomography angiography (CTA) and magnetic resonance arteriogram (MRA) and portal venography were performed. Color Doppler exam of the portal vein was performed followed by administration of Lumason, a microbubble US contrast agent. RESULTS: Magnetic resonance arteriogram, CTA, and color Doppler exam at the time of initial presentation was unremarkable without obvious vascular malformation within the limits of motion degraded exam. At 8-month follow-up, esophagogastroduodenoscopy revealed a vascular malformation in the distal esophagus which was sclerosed. At 6 month after sclerosis of the lesion, portal venography revealed occlusion of the portal vein with extensive collateralization. Color Doppler revealed subtle hyperarterialization and periportal collaterals. CEUS following color Doppler exam demonstrated extensive enhancement of periportal collaterals. Repeat color Doppler after contrast administration demonstrated extensive Doppler signal in the collateral vessels, suggestive of cavernous transformation. CONCLUSIONS: We describe a case of cavernous transformation of the portal vein missed on initial color Doppler, CTA and MRA, but detected with contrast-enhanced ultrasound technique. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40477-018-0288-3) contains supplementary material, which is available to authorized users.